Factors Associated With The Use Of Implant Contraceptive Devices In Women Of Reproductive Age - Anjarwati, Nurul; Nisa, Nurul Khoirun; Pratama, Rika Yuanita (Jurnal Surya, 2023)
Introduction: The implant contains levonogestrel, the advantage of this method lasts up to five years, once the contraceptive is taken the fertility will return soon. The side effect of using this contraceptive implant is weight gain because the hormones contained can stimulate the appetite control center in the hypothalamus. This study aims to find out the factors associated with the use of implanted contraception in women of childbearing age (WUS)Method: This research is a cross-sectional quantitative study with the Simple Random Sampling technique. The results of the study were analyzed using a statistical test, namely Chi-Square to see the relationship with the use of implanted contraceptive devices in women of childbearing age (WUS)Results: The results showed that there was a relationship between the use of implanted contraceptives and attitude (p-value = 0.002), access to health services (p-value = 0.033), the role of health workers (p-value = 0.033), and there was no relationship between contraceptive use implant with Age (p=0.331), Education (p-value=0.444), Knowledge (p-value=0.148)Conclusion: There is a relationship between attitude, access to health services, the role of health workers, husband's support and there is no relationship between age, education, knowledgeKeywords: Factors, implant contraception, women of childbearing age